TQM practices and knowledge sharing: An empirical study of Malaysia’s manufacturing organizations - Ooi, Keng-Boon; Cheah, Weng-Choong; Lin, Binshan; Teh, Pei-Lee (2012)
The purpose of this paper is to examine the multidimensionality of TQM practices and its relationship with knowledge sharing as perceived by middle management employees in Malaysia's ISO 9001:2000 certified firms of manufacturing sectors. The data which were collected from a survey of 129 middle management employees in Malaysia were used to test the proposed research framework. Furthermore, confirmatory factor analysis was performed to evaluate the reliability and validity of the measurement model, and the structural analysis was used to examine the research framework. The analytical results revealed that training and development, customer focus, and teamwork showed a positive association with middle management employees' knowledge sharing. This analysis is vital for senior managers of TQM companies that want to establish a knowledge sharing capability. Senior managers could focus their efforts on implementing TQM practices for building competitive knowledge sharing competencies.